Odpowiedzi

2010-02-11T19:43:13+01:00
A) 3(2*-2x+3)-2(2*-5x-1)=3(4-2x+3)-2(4-5x-1)=12-6x+9-8+10x+3=4x+7
b) -0,1(2ab-10)+10(o,1-2ab+0,1*)=-0,2ab+1+1-20ab+0,1=-20,2ab+1,1
2010-02-11T19:44:12+01:00
A) 3(2*-2x+3)-2(2*-5x-1)=3(4-2x+3)-2(4-5x-1)=12-6x+9-8+10x+2=4x+15
b) -0,1(2ab-10)+10(o,1-2ab+0,1*)=-0,1(2ab-10)+10(0,1-2ab+0,01)= -0,2ab+1+1-20ab+0,1=-20,2ab+2,1

Co do tego drugiego to nie jestem pewna, bo dziwny wynik wyszedł.
2010-02-11T19:45:03+01:00
A)

3(4-2x+3)- 2(4-5x-1)=
12-6x+9-8-10x-2=
11-16x



b)

-0,1(2ab-10)+10(0,1-2ab+0,1*)=
-0,2ab-1+1-20ab+1=
1-20,2ab